Streaking to success: The effects of highlighting streaks on student effort and learning - Raphaëlle Aulagnon; Julian Cristia; Santiago Cueto; Ofer Malamud (Inter-American Development Bank (IDB), 2024)
We examine whether highlighting streaks encourages 4th to 6th grade students in Peru to increase their use of an online math platform and improve learning. Sixty thousand students were randomly assigned to receive messages that i) highlighted streaks, ii) provided personalized reminders with positive reinforcement, or iii) provided generic reminders, while others were assigned to a control group. Highlighting streaks and providing personalized reminders significantly increased platform use compared to generic reminders and the control group, with streaks more effective on the intensive margin and personalized reminders more effective on the extensive margin. Highlighting streaks also significantly improved math achievement compared to the control group.
Keywords: I21; I25; D91; 330; Streaks; Education; Math achievement; Online